Infeksi Cacing Usus pada Anak Sekolah Dasar Negeri Cilincing 06 Jakarta Utara sebelum dan sesudah Pengobatan Albendazol Dosis Tunggal - Rizqi Putra Pratama; Monica Puspa Sari; Esther Sri Majawati (Jurnal Kedokteran Meditek, 2020)
In Indonesia, the number of helminthiasis is still significant. A person is more easily infected with intestinal worms at school age than adult. This study aims to determine the effectiveness of a single dose of Albendazole 400 mg against worm infections in children who were positive of intestinal worms. Subjects for this study were school children of Cilincing 06 Elementary School, North Jakarta. Microscopic examination was conducted using the Kato Katz method using fresh feces. This study uses an experimental pre-post study method. Respondents were selected based on a simple random sampling and data analysis was carried out using the IBM SPSS program version 23.0. Before treatment, out of 82 students, there were 5 students (6.1%) who were positively infected with intestinal worms (Ascaris lumbricoides 3.7% and Trichuris trichiura 2.4%). Students who were positive for intestinal worms were given a single dose of Albendazole 400 mg. Following this treatment, no infection of Ascaris lumbricoides was found (0%), however Trichuris trichiura infection was still found (1.2%). Statistical data analysis using Mc Nemar test obtained p value> 0.05. Statistical test results showed no significant change in the results before and after treatment of Albendazole 400mg single dose.